Ang mabahong prutas - Ordinario, Mary Ann (ABC Educational Development Center, 2018)
Durian, the King of Fruits, is also infamous for its spiky skin and very strong odor. Legend has it the durian originally had smooth skin and smelled like freshly bloomed flowers on a sunny day. What could possibly have happened for it to change so drastically?--Pumplepie: books and happiness.